Efficacy of oral irrigators compared to other interdental aids for managing peri-implant diseases: a systematic review - Gargi Gandi; Bhoomika Sai Laxmi Masanam; Ananya Sudhakaran Nair; Nidhi Semani; Aditi Chopra; Venkitachalam Ramanarayan (BDJ Open)
Abstract Objective Peri-implant diseases (peri-implant mucositis and peri-implantitis) are inflammatory conditions that affect the peri-implant tissues and are induced by microbial biofilms (dental plaque) formed around the implant. Removal of biofilm is the fundamental step in managing peri-implant diseases. Interdental cleaning aids such as interdental brush, unitufted brush, or oral irrigation along with regular toothbrushing are recommended for effective plaque control around implants. The present systematic review aims to evaluate the efficacy of home use of oral irrigators compared to other plaque control methods for managing peri-implant diseases. Method This systematic review has been prepared using the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols (PRISMA) checklist. Five databases were searched using the following keywords: “Peri-implantitis” OR Periimplantitis OR “Peri-implant disease” OR “Peri-implant Mucositis” AND “Oral irrigation” OR “Oral Irrigator” OR Waterpik OR “Interdental irrigation” OR “Oral Spray” OR “Oral Irrigants”. Results Oral irrigator along with mechanical brushing was found to be more effective than mechanical brushing alone in reducing the plaque index (PI), gingival index (GI), and bleeding on probing (BOP). No statistically significant difference in improvement in quality of life and patient satisfaction with regard to comfort and ease of use was noted upon using mechanical toothbrushing alone and an oral irrigator. Implant sites where an oral irrigator was used showed more reduction in BOP (81.8% vs 33.35%) compared to sites where the floss was used (P = 0.0018). The levels of the red and orange complex bacteria in the peri-implant biofilm were lower with the use of an oral irrigator than with toothbrushing alone. Conclusion Oral irrigators along with toothbrushing were found to be more effective in removing microbial plaque around implants and controlling peri-implant inflammation compared to mechanical brushing alone. The reduction in BOP was better with the use of oral irrigation compared to floss and interdental brush.